The efficacy of a non-leaching antibacterial central venous catheter - a prospective, randomized, double-blind study - Krikava, Ivo; Kolar, Martin; Garajova, Barbora; Balik, Tomas; Sevcikova, Alena; Roschke, Ingolf; Sevcik, Pavel (Biomedical papers, 2020)
Background: Antimicrobial coatings of central venous catheters (CVC) have the potential to reduce the risk of infectious complications. The aim of this study was to examine the efficacy of a catheter with a non-leaching antimicrobial coating against catheter colonization and bloodstream infections (BSI). Methods: The study was conducted in two centers using a prospective, randomized, double-blind and controlled design (680 intensive care patients; a protective CVC (Certofix(R) protect) or a standard CVC (Certofix(R)). Primary objectives were the rates of catheter colonization and BSI in the two groups. Other baseline demographics, APACHE II score, insertion site, location of CVC placement (ICU or theatre), indwelling time and length of ICU stay were comparable for both groups. Results: While the rate of catheter colonization between the coated and uncoated CVC (17.4% vs. 18.7%, P=0.7477) and the rate of microbiologically confirmed catheter associated infections were similar (1.4% vs. 1.9%, P=0.7521), the coated CVC showed a significantly lower incidence of BSI (2.0% vs. 6.5%, P=0.0081) and a significantly lower mean incidence of BSI per 1000 catheter days (3.2 vs. 8.3, P=0.0356). Conclusion: The non-leaching antibacterial coating of the protective catheter was effective in reducing the incidence of BSI but not the rate of catheter colonization. However, the incidence of BSI is a better surrogate marker for the risk of developing clinical signs of infection suggesting that use of the non-leaching protective catheter is effective in this regard. Trial number: ClinicalTrials.gov (ID: NCT00555282), https://clinicaltrials.gov/show/NCT00555282
Keywords: antimicrobial; CVC; non-leaching; catheter-related bloodstream infections